Biliary-Caval Fistula following Y90 Radioembolization - Hall, Alexander D.; White, Sarah B.; Rilling, William S. (Seminars in Interventional Radiology, 2021)
The safety of radioembolization with yttrium-90 (90Y) is well documented and major complications are rare. Previous studies have demonstrated that biliary complications following 90Y, including bile duct injury and hepatic abscess formation, occur at an increased rate in patients who have had prior biliary surgery and interventions. This article reviews a case of a patient who developed recurrent cholangitis and sepsis as well as a biliary-caval fistula following radioembolization. Additionally, we review current data regarding biliary complications following radioembolization in patients with prior biliary intervention.
Keywords: radioembolization; 90Y; liver-directed therapy; cholangitis; biliary infection; interventional radiology